THE IMPACT OF SPORT CLIMBING ON SOME MORPHOLOGICAL CHARACTERISTICS AND MOTOR ABILITIES IN CLIMBERS OF 14 YEARS OF AGE - Blaž Jereb; Stojan Burnik (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2009)
The objective of our research was to identify the impact of sport climbing on some morphologic characteristics and motor abilities in climbers. The sample group consisted of 19 climbers, who trained climbing for one year beside their regular physical education after the initially survey was made, and 72 nonclimbers, who's only sport activity was their regular physical education. At the time of the test, climbers as well as nonclimbers were 14 years of age. The measurement included all the variables from the Physical education chart. Data were processed with statistical programme package SPSS for Windows. The result of analysis of covariance show that after a year long period of sport climbing statistically significant differences were shown in the results of t he test Polygon backwards in favour of the experimental group. It is also possible to observe a trend towards better results of the experimental group in the tests Skin fold thickness of the upper arm and Bend and touch on bench. The nonclimbers achieved larger differences than climbers in torso lifting and 600 m run.